Investigating the Response of Light-Frame Wood Stud Walls with and Without Boundary Connections to Blast Loads - Viau, Christian (Université d'Ottawa / University of Ottawa, 2016)
Most of the research on high strain rate effects on wood since the 1950s has been on impact loading. Very limited work has been conducted on full-scale wood specimens under blast loading. In North America, the prevalence of these structures makes them susceptible to unintended blast effects. The question on how to retrofit and protect these structures against blast loads has still not been addressed adequately, and design provisions for new wood structures against blast are not comprehensive. Far-field explosion effects were simulated using the University of Ottawa shock tube. Twenty-five light-frame wood stud walls were tested dynamically. The research program aimed to determine the response of light-frame wood stud walls to blast loads that correspond to the heavy to blow-out damage levels. The results showed that, under idealized simply supported end conditions, the stud walls failed in flexure. Under heavier loads, ripping of sheathing commonly used in light-frame wood structures was observed, which caused premature failure of the assembly because the load was not fully distributed to the studs. The use of stiffer sheathing or reinforcing the sheathing provided a better load path and the wall was capable of reaching its full capacity. The effect of using realistic boundary connection details was investigated, and the results showed that typical connection detailing performed poorly under blast loads. Designed steel brackets connecting the studs to the rim-joist allowed for the studs to reach their full capacity. An analytical single degree-of-freedom model was generated using material properties obtained from static testing. The model was validated using the experimental results from the shock tube testing. Also, a catcher system consisting of welded-wire-mesh was incorporated into the wall system in order to diminish debris throw.
Keywords: wood; blast; light-frame; single degree-of-freedom; shock tube; high strain rates; connections; retrofits; sequence of failure; debris